Monoclonal antibody-based immunoassays for cyprodinil residue analysis in QuEChERS-based fruit extracts. (15th November 2015) - Esteve-Turrillas, Francesc A.; Abad-Somovilla, Antonio; Quiñones-Reyes, Guillermo; Agulló, Consuelo; Mercader, Josep V.; Abad-Fuentes, Antonio
Highlights: A battery of high-affinity monoclonal antibodies to cyprodinil has been generated. Two immunoassays in different formats have been characterized and developed. QuEChERS-based strawberry extracts were diluted in water and analyzed by cELISA. Deming regression showed good agreement between immunoassays and UPLC–MS/MS. Abstract: Cyprodinil is among the most common agrochemical residues found in highly perishable fruits, such as strawberries. In the present study, high-affinity monoclonal antibodies to this anilinopyrimidine fungicide were raised for the first time with the aim to produce valuable immunochemical analytical assays. Cyprodinil bioconjugates and the generated novel monoclonal antibodies were employed for sensitive competitive immunoassay development in two different formats. The limits of detection of the optimized assays were 20 and 30 ng L −1 for the indirect and direct assay, respectively. Influence over assay parameters of different physicochemical factors was studied. Strawberry samples were extracted following the recommended QuEChERS procedure for pesticide residues in food, and analyzed by the optimized immunoassays. Recoveries and coefficients of variation from fortified samples were within standard values. In addition, the obtained immunochemical results with naturally contaminated samples were statistically comparable, according to Deming regression analysis, to those of a reference chromatographic method.